Bots, fake comments, and E-rulemaking: the impact on federal regulations. Issue 11 (18th August 2022) - Rinfret, Sara; Duffy, Robert; Cook, Jeffrey; St. Onge, Shane
ABSTRACT: E-rulemaking, adopted over a decade ago, allows federal agencies to use technology to provide electronic submission of public comment for a rule through the Federal Register . Some scholars suggested that this could create a space for deliberative democracy and improved regulatory outcomes. Yet, has e-rulemaking achieved its goals? The Federal Communications Commission's (FCC) Net Neutrality Rule received millions of fake public comments submitted by "bots, " many from outside the U.S. The central focus of this exploratory project is to use the e-rulemaking literature as a descriptive baseline to examine original interview data from 32 agency rule-writers and program managers from the Environmental Protection Agency (EPA). The EPA, from 2002–2019, served as the managing partner of e-rulemaking initiatives. Our focus is to determine what, if anything, the agency did to identify bots or to screen out fake comments. The findings suggest the 2002 E-Government Act did not anticipate the emergence of bots and thus fails to provide agencies with sufficient guidance on how to identify and treat bots and fake comments.